Using AIC In Model Choice about Entrepreneurial Attitude Orientation - Thi Ngan, Nguyen (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to identify the factors that influenced the Entrepreneurial Attitude Orientation. Survey data were collected from 220 respondents living at HCM City, Vietnam. The research model was proposed from the studies of Entrepreneurial Attitude Orientation. The reliability and validity of the scale were evaluated by Cronbach’s Alpha, Average Variance Extracted (Pvc), and Composite Reliability (Pc). The model selection of AIC showed that Entrepreneurial Attitude Orientation was impacted by two components of the Entrepreneurial Attitude Orientation included Innovation and Personal control.